Churn flow in high viscosity oils and large diameter columns. (March 2018) - Mohammed, Shara K.; Hasan, Abbas; Dimitrakis, Georgios; Azzopardi, Barry J.
Highlights: Churn flow regime is introduced in very high viscosity liquids and large diameter columns. Advanced tomographic method is employed to study the phase distribution in the pipe cross section. High activity regions of liquid bridges (churn regions) are created from the drained film around the long Taylor bubbles. Transition to churn flow starts when the length and frequency of churn regions increase in the end of slug flow. Churn flow consists of a wavy open gas core of low void fraction with a possibility of creating a very long bubble. Abstract: Churn flow is an important intermediate flow regime occurring in between slug and annular flow patterns in two-phase flow, with profound implications in chemical and petroleum industry. The majority of studies to date in churn flow have been carried out mainly using water or liquids of low viscosities and limited information exists regarding the behaviour of high viscosity liquids which resemble realistic process conditions. In this paper, a study that investigated churn flow and its characteristics in high viscosity oils (360 and 330 Pa.s) and large diameter columns (240 and 290 mm) is presented for a first time. Transition to churn flow regime starts when the structure velocity, length and frequency of the liquid bridges, which appear at the end of slug flow, increase. In churn flow, gas flows at the core of the oil column with a wavy passage, leaving the top surface open to atmosphere with a possibility of creating a very long bubble. The average length of the bubbles seen to decrease with increasing the gas flow rate. While, no considerable change is observed in void fraction, structure velocity and film thickness at this flow pattern.